2012
DOI: 10.5251/ajsir.2012.3.3.157.165
|View full text |Cite
|
Sign up to set email alerts
|

The Dilemma of Falciparum Malaria and Telecommunications in Northeastern Nigeria

Abstract: The study of the prevalence of malaria, in relation to interpersonal communication ownership amongst adults and pregnant women in Adamawa. A database was designed at the American University of Nigeria, in collaboration with the Federal Medical Center in Yola. The database comprised patient information on age, sex, and the species of malaria, parasitaemia levels and ownership of interpersonal communication. For females, pregnancy status was noted. Over fortythree percent of all 1126 patients screened had malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In as much that malaria has the tendency of occurring with other infections especially the ones that has similar symptoms. Some of the notable symptoms include fever, malaise and weakness (Pam et al, 2015), fever, chills, headache, nausea, anorexia and anemia (Tyndall et al, 2012). Salmonella species from blood specimens of malaria patients 12% Nsukka, Nigeria.…”
Section: Medical Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…In as much that malaria has the tendency of occurring with other infections especially the ones that has similar symptoms. Some of the notable symptoms include fever, malaise and weakness (Pam et al, 2015), fever, chills, headache, nausea, anorexia and anemia (Tyndall et al, 2012). Salmonella species from blood specimens of malaria patients 12% Nsukka, Nigeria.…”
Section: Medical Conditionmentioning
confidence: 99%
“…Malaria infection caused by Plasmodium falciparum is more perilous during pregnancy (Adefioye et al, 2007) compare to other species of Plasmodium. Pregnant women and infants with malaria are high risk group (Enato et al, 2007;Tyndall et al, 2012) causing maternal, perinatal and fetal morbidity and mortality (Enato et al, 2007). Furthermore, Alaku et al (2015) also reported that pregnant women form a high risk group for malaria infection.…”
Section: Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been estimated to cause death of two million children globally per annum (Okafor and Oke-Oso, 2012). Globally, nearly 50% of the world's 3.28% to 3.40% billion people live in areas at risk of malaria infections (Tyndall et al, 2012, Orok et al,2016, which are distributed in 106 nations (Nigeria Fact Sheet, 2011 ). Okonko et al, 2010, reported that 300 to 500 million clinical cases occur globally leading to over 1 million deaths.…”
mentioning
confidence: 99%